PERAN BADAN NARKOTIKA NASIONAL DALAM KEBIJAKAN HUKUM PIDANA MENANGANI KASUS NARKOTIKA ANAK DIBAWAH UMUR - Ica Ica lanye enjelina Sitohang; Nurmaya Nurmaya R A Simanjuntak (Judge : Jurnal Hukum, 2025)
Drug abuse (narcotics) among minors is a form of crime that has a serious impact on the future of the nation's generation. The purpose of this study is to analyze how the National Narcotics Agency (BNN) implements criminal law policies related to narcotics transaction cases involving minors and also to find out the factors that cause narcotics abuse among them. The method used in this study is normative juridical with a legal and conceptual approach. The findings of the study show that BNN has an important role in three main aspects, namely prevention, law enforcement, and rehabilitation. However, the effectiveness of the implementation of the policy still encounters various challenges, such as limited human resources, lack of rehabilitation places for adolescents, and weak cooperation between the institutions involved. Efforts to overcome this problem are carried out with promotional, preventive, curative, rehabilitative, and repressive approaches that are carried out continuously. In order for the implementation of criminal law policies to be more effective, it is necessary to increase cross-sector cooperation and strengthen the education and rehabilitation function for children who use narcotics.